Friday

April 18, 2014

April 18, 2014

Posted by **baller** on Tuesday, February 5, 2013 at 11:29am.

e5q41

- math -
**Steve**, Tuesday, February 5, 2013 at 11:34am2y^2 + 4y - 6 = 1

2y^2 + 4y - 7 = 0

y = 1/2 (-2 ± 3√2)

**Related Questions**

Algebra Problem - I've gotten confunsed. Please help. Solve: 2y-a = a + 3b ____ ...

linear algebra - Use an inverse matrix to solve each system of linear equations...

linear algebra - Use an inverse matrix to solve each system of linear equations...

linear algebra - Use an inverse matrix to solve each system of linear equations...

maths - use the substitution method to solve the linear system. 1. 3x=9 -x+2y=9 ...

math - did i solve for y correctly? 1/2y+2-y=1 -1/2y+2=1 -1/2y=1-2 -1/2y=-1 y=-1...

Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...

algebra - how do I do this Solve for x. 3x – 2y = 6 Add 2y to both sides and ...

Algebra - I need help on this one too, please. Solve for X. 3x-2y=6 I got x=6+2y...

Algebra - To solve the system of equations, which expression could be ...